Razumevanje vloge medicinske sestre pri spremembi življenjskega sloga posameznikov, v preteklosti odvisnih od prepovedanih drog - Kadenšek, Klavdija (Obzornik zdravstvene nege, 2017)
Introduction: In the health care of individuals addicted to illegal drugs the relationship between the individual and a nurse is highly significant. The aim of this research was to study the role of a nurse in facilitating lifestyle change among former illicit substance abusers. Methods: This research is based on qualitative research methodology. A semi-structured interview was used. A purposive sample (n = 8) was implemented. It included four individuals who had previously been addicted to illegal drugs and four nurses working in the field of drug addiction. Data processing was carried out with content analysis of qualitative empirical research thus ensuring reliability of the research. Results: Individuals recognise the role of a nurse in the non-judgemental support that they offer their patients. Nurses provide a safe environment in which individuals may trust them with their intimate experiences. The trustworthy relationship is created gradually and is based on selfless acceptance of an individual, trust and empathy. In order to effectively encourage an individual to changes their lifestyle, nurses need to obtain current knowledge in counselling and motivating. Discussion and conclusion: Participants in the research see the solution particularly in the presence of a nurse as they provide the individual with support and act as a counsellor. According to the nurses who participated in the research, nurses who work in the field of drug addiction expect more targeted activities regarding lifestyle. Since this field is poorly researched in Slovenia, beneficial and necessary activities of health care employees dealing with drug addiction should be defined.
Keywords: družina; epidemiologija; epidemiology; family; health; heroin; nursing care; rehabilitacija; rehabilitation; vocational rehabilitation; zdravje; zdravstvena nega